A critical political ecology of consensus: On "Teaching Both Sides" of climate change controversies. (October 2015) - Colston, Nicole M.; Vadjunec, Jacqueline M.
Highlights: "Teach the controversy" campaigns increasingly couple evolution and climate change. Oklahoma science teachers face challenges to climate change consensus via classroom pushback. Critical political ecology highlights teachers in the coproduction of climate change consensus. Everyday acts of resistance are used to negotiate and manage anti-science pushback in classrooms. Abstract: In the United States, contemporary anti-science education coalitions are increasingly linking climate change and evolution using "teach the controversy" campaigns. Awareness of this political phenomena raises questions about the extent to which portrayals of global warming predictions as mere knowledge claims undermine efforts to increase public understanding of scientific consensus about global warming. This paper uses a critical political ecology framework to explore the problematization of climate change consensus located and performed across discourses of secondary science teaching and learning. Theories of resistance are used to analyze teachers' everyday experiences with classroom pushback about climate change. Data collection included key informant interviews with state science education stakeholders and on-line survey of 5th–12th grade science teachers in Oklahoma, USA. The article synthesizes the situated discourses of Oklahoma science teachers' and their attitudes about teaching climate change in the face of public controversy. Our analysis demonstrates teachers marginalized by anti-science controversies but engaged in everyday acts of resistance to political, ideological, and religious norms. Most notably, science teachers re-purpose "teach the controversy" frames as a way to introduce climate change where it might not otherwise be included. We argue that, contextualized within a history of contestation over the teaching of evolution, the practice of teaching 'both sides' is an important boundary ordering device that bridges convinced and skeptical discourses in the classroom. This research informs new roles and possibilities for science education on global environmental change by reminding climate scientists, educators, and policy advocates that all climate change knowledge is coproduced.